RANCANG BANGUN GAME EDUKASI AKSARA JAWA BERBASIS ANDROID (Information Technology and Telematics, 2016)
Abstract --- Educational game very interesting if used in teaching and learning. Is currently learning about Indonesian culture, especially Javanese still use textbooks guide, so that children feel bored quickly. The development of today's technology can create a companion application lets kids learn to recognize and write a Java script that can be made in the form of educational games. This educational game created with Corona Software Development Kit for Windows operating systems. This application uses the keyboard mapping of Latin letters to the Java script font type hanacaraka. Educational game application in Android mobile form is a solution that can answer the shortcomings of the existing learning system. Keyword --- Educational Game, Java script, Android